HUBUNGAN USIA IBU, GRAVIDITAS, RIWAYAT PRE-EKLAMPSIA BERAT DI RSUD. KABUPATEN BEKASI PERIODE JUNI 2015- JUNI 2016 - Luthfiyani, Syifa Aulia; Reksoprodjo, Mariono; Anisah, Anisah (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2017)
Pre-eclampsia/Eclampsia is the second largest cause of maternal death after postpartum hemorrhage. There are some risk factors that influence the occurrence of pre-eclampsia/eclampsia. The aim of the research was to analyze the correlation between risk factors and find the most influence factors to the incidence of severe pre-eclampsia in RSUD District Bekasi. This case control study research done by using secondary data by looking at the data in patient medical records in RSUD District Bekasi period June 2015 - June 2016 and then analyzed using univariate, bivariate with Chi-square and multivariate logistic regression. Sampling method using simple random sampling technique. The results of the bivariate analysis showed there was a significant relationship between gravidity, obesity and history of pre-eclampsia with severe pre-eclampsia with each value of p = 0.022 (OR: 0.251), p = 0.002 (OR: 6,923) and p = 0.0001 (OR: 9.273). Multivariate analysis showed that history of pre-eclampsia and obesity are factors that most influence to the occurrence of severe pre-eclampsia. There was a significant relationship between gravidity, history of pre-eclampsia and obesity with severe pre-eclampsia. Primigravidas 2.51 times higher risk, history of pre-eclampsia positive 6,923 times higher and obesity 9.273 times higher more at risk of developing severe pre-eclampsia.